Modelli semplificati di analisi delle sorgenti di rischio e del sovraccarico biomeccanico nel settore artigiano: esperienze applicative nel comparto del legno per la produzione di botti / Simplified models of analysis of the sources of risk and biomechanical overload in craft industries: application experience in wooden barrel making - Pressiani, S. (La Medicina del Lavoro, 2011)
«Simplified models of analysis of the sources of risk and biomechanical overload in craft industries: application experience in wooden barrel making». Background: Barrel making is an ancient art evidence of which is found in paintings from the Egyptian era in the Mediterranean civilizations, and since it was an ideal shipping container its use spread quickly and on a wide scale. Methods: The study was conducted in a small high quality craft industry, applying the method which is the topic of this volume, i.e., risk pre-mapping by which it is possible to identify the presence or absence of occupational risk and any need for further evaluation. Results: The study showed the presence of health risks for workers, which were mainly physical (noise, vibrations produced by machinery and equipment typical of the craft, and risks from hardwood dust, in addition to the traditional risks of biomechanical overload of the upper limbs. Discussion: Today, the barrel maker is a professional craft of excellence and quality, dedicated to the creation of large barrels and vats, using woods of different essences depending on the organoleptic qualities that it is desired should influence the final flavour of the wine: the manual art and the equipment are ancient but the technology used to achieve the final product is necessarily advanced. Conclusion: So far issues of safety and health risks related to this type of industry have received little attention and the risks poorly evaluated, with the possibility that occupational diseases may occur among the operators, particularly of the skeletal-muscular type.